Analysis Service Quality In The Success Of The Bandung City Dpmptsp As The Best Performance Dpmptsp In West Java - Fadjar Trisakti; Disa Maulida Insani; Aqshal Kiswa Fadillah; Dian Octaviani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2023)
Abstract Citizens have the right to receive quality public services from the state (bureaucracy). DPMPTSP Bandung City itself succeeded in winning first place in the Best Performance Assessment of Capital Investment and One-Stop Integrated Services for Regencies and Cities in West Java in 2023.Based on this phenomenon, researchers were moved to conduct related researchServices Quality (Service Quality) at the Bandung City DPMPTSP with the aim of analyzing and finding out what strategies or methods are used by the Bandung City DPMPTSP so that it succeeds in becoming first place in the best performance assessment in West Java Province in 2023. The type of research used in This research is a type of descriptive research with a qualitative approach. Meanwhile, the analytical tool used is that the Bandung City DPMPTSP has provided very good service quality so far to the community, this can be proven by the achievement of all the indicators put forward by the service quality theory of Zeithaml, Parasuraman & Berry. Based on the results of the researcher's analysis, it can be seen that the Bandung City DPMPTSP has succeeded in providing good quality service to the community so far, this can be proven by achieving all service quality indicators proposed by Parasuraman, Zeithaml and Berry. Keywords: Community, DPMPTSP, Service Quality